2011
DOI: 10.2478/s11535-011-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Costs of reproduction in life history of a perennial plant Carex secalina

Abstract: We tested a hypothesis based on life history theory that examines reproductive costs incurred by individuals in consecutive years of their life. A multi-year dataset of resource allocation to vegetative and reproductive structures was analysed in Carex secalina — a perennial, monoecious sedge, reproducing only sexually. In a four-year garden experiment, we assessed above-ground biomass at the end of each season and reproductive allocation expressed as the total length of male and female spikes. The study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Contrary to our results, competition between fruit load and subsequent vegetative development has been reported in apple where heavy fruit load decreases vegetative development ( Jonkers, 1979 ; Forshey and Elfving, 1989 ) and secondary growth ( Lauri et al, 2010 ) in the same year. Similarly, the increase in plant biomass was lower when more reproductive structures were produced in the previous year in Carex secalina , a perennial monoecious species ( Bogdanowicz et al, 2011 ). Moreover, several studies have found that there are less new shoots during years of high fruit production than during years of low fruit production at the tree scale in pistachio ( Weinbaum et al, 1994 ; Brown et al, 1995 ; Rosecrance et al, 1996 ; Picchioni et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our results, competition between fruit load and subsequent vegetative development has been reported in apple where heavy fruit load decreases vegetative development ( Jonkers, 1979 ; Forshey and Elfving, 1989 ) and secondary growth ( Lauri et al, 2010 ) in the same year. Similarly, the increase in plant biomass was lower when more reproductive structures were produced in the previous year in Carex secalina , a perennial monoecious species ( Bogdanowicz et al, 2011 ). Moreover, several studies have found that there are less new shoots during years of high fruit production than during years of low fruit production at the tree scale in pistachio ( Weinbaum et al, 1994 ; Brown et al, 1995 ; Rosecrance et al, 1996 ; Picchioni et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Culm length and leaf width characterize the studied species vegetatively; lateral inflorescence unit length, utricle length and number of utricles per lateral inflorescence unit characterize them reproductively. We interpret lateral inflorescence unit length as a surrogate for the total investment of plants in each inflorescence unit (Bogdanowicz et al. , 2011), and utricle length and number of utricles per inflorescence unit as estimates of the rate of production of propagules per inflorescence unit and their sizes (see r / K strategies in Pianka, 1970).…”
Section: Descriptionmentioning
confidence: 99%
“…The cultivated plants of C. secalina from the described garden experiment were also used as maternal plants in our previous studies to provide seeds for germination experiments (Lembicz et al 2011) and to estimate the costs of reproduction based on total shoot production (Bogdanowicz et al 2011).…”
Section: Garden Experimentsmentioning
confidence: 99%